Improving the demand for birth registration: a discrete choice experiment in Ethiopia. Issue 5 (21st May 2020) - Yihdego, Mahari; Amogne, Ayanaw; Desta, Selamawit; Choi, Yoonjoung; Shiferaw, Solomon; Seme, Assefa; Liu, Li; Helleringer, Stéphane
Abstract : Introduction: Birth registration remains limited in most low and middle-income countries. We investigated which characteristics of birth registration facilities might determine caregivers' decisions to register children in Ethiopia. Methods: We conducted a discrete choice experiment in randomly selected households in Addis Ababa and the Southern Nations, Nationalities, and People's Region. We interviewed caregivers of children 0–5 years old. We asked participants to make eight choices between pairs of hypothetical registration facilities. These facilities were characterised by six attributes selected through a literature review and consultations with local stakeholders. Levels of these attributes were assigned at random using a fractional design. We analysed the choice data using mixed logit models that account for heterogeneity in preferences across respondents. We calculated respondents' willingness to pay to access registration facilities with specific attributes. We analysed all data separately by place of residence (urban vs rural). Results: Seven hundred and five respondents made 5614 choices. They exhibited preferences for registration facilities that charged lower fees for birth certificates, that required shorter waiting time to complete procedures and that were located closer to their residence. Respondents preferred registration facilities that were open on weekends, and where they could complete procedures in a single visit. In urban areas, respondents also favoured registration facilities that remained open for extended hours on weekdays, and where the presence of only one of the parents was required for registration. There was significant heterogeneity between respondents in the utility derived from several attributes of registration facilities. Willingness to pay for access to registration facilities with particular attributes was larger in urban than rural areas. Conclusion: In these regions of Ethiopia, changes to the operating schedule of registration facilities and to application procedures might help improve registration rates. Discrete choice experiments can help orient initiatives aimed at improving birth registration.